Analyzing critical success factors using blockchain based framework for intelligent transportation systems - Mutahhar, Ahmad Yahya; Khanzada, Tariq Jamil Saifullah; Shahid, Muhammad Farrukh (Frontiers in Blockchain, 2025)
This study examines the incorporation of blockchain technology into Saudi Arabia's Intelligent Transportation Systems (ITS), concentrating on enhancing the bus permission procedure for religious mass gatherings in Makkah. The research illustrates how blockchain might improve the security and operational effectiveness of transportation management for major events. The research used a weighted significance methodology and Decision-Making Trial and Evaluation Laboratory (DEMATEL) analysis to identify the critical success factors (CSFs) influencing transportation at religious events. The research illustrates the strong interrelation of the CSFs, emphasizing the notable enhancement in transparency and efficiency in the approval and management processes using blockchain-based solutions. The research examines the impact of reformulated CSFs on the proposed blockchain-based transportation framework (BTF), emphasizing key domains such as people (P_1), technology (P_2), the environment (P_3), and organization (P_4). The findings indicate that blockchain-related CSFs exhibit the greatest influence, which is 21.62, while financial CSFs demonstrate the least influence of 0.25. This research significantly addresses current system limitations and stimulates wider blockchain usage inside Intelligent Transportation Systems by developing a thorough mathematical model. This paper presents a strategy framework for the successful management of large-scale transportation difficulties with blockchain technology, assuring optimum operations in organizational and environmental contexts.